Acute thyroid swelling and elevated C reactive protein. (21st August 2013) - Nebiker, Christian A; Delko, Tarik; Zulewski, Henryk; Oertli, Daniel
Abstract : A 34-year-old lady presented with a painful swelling of the left thyroid lobe since 1 week and elevated C reactive protein (CRP) above 100 mg/L. An ultrasound examination revealed a thyroid cyst with partly solid component, suitable with a haemorrhage into a cyst. The serum thyroid stimulating hormone (TSH), as well as peripheral thyroid hormones, was in the normal range. The acute swelling could be well explained by a haemorrhage, but not an elevated CRP. Her medical history was uneventful apart from a tooth extraction 2 weeks ago due to an infection. Therefore, our hypothesis was a haemorrhage into a pre-existing thyroid cyst during bacteraemia caused by the tooth infection. Conservative treatment with the aim of delayed hemithyreoidectomy failed due to a second episode of haemorrhage. During surgical resection pus drained out of the cyst and the histological report afterwards confirmed our tentative diagnosis. The patient was discharged 2 days later.